Pengaruh Presepsi Keamanan Bukti Transaksi Manual Terhadap Loyalitas Mahasiswa Sebagai Nasabah BMT Universitas Sains Islam Al-mawaddah Warrahmah Kolaka - Anggun Ade Fatrisia; Amanda Hirmayani (AKUNTANSI 45, 2025)
This study aims to analyze the effect of security perception on student loyalty as customers of Baitul Maal wat Tamwil (BMT) at Universitas Sains Islam Al-Mawaddah Warrahmah (USIMAR) Kolaka. The research focuses on how students perceive the security of manual transaction receipts provided by the BMT and how these perceptions influence their loyalty in continuing to use its services. The study employs an associative quantitative approach using simple linear regression analysis. A total of 222 students were selected through purposive sampling. Data were collected through closed-ended questionnaires using a Likert scale and documentation. The results show that perceived security has a positive and significant influence on student loyalty, with a significance value of 0.024 and a coefficient of determination (R²) of 0.451. This indicates that approximately 45.1% of the variation in student loyalty can be explained by their perception of the security of the manual transaction evidence provided by the BMT. These findings highlight the importance of developing a more secure and reliable transaction documentation system to enhance customer loyalty in academic environments.